Growth of SnO2 nanocrystals co-doped with Eu3+ for highly enhanced photoluminescence in mesoporous silica glasses. Issue 6 (18th January 2019) - Chen, Ping; Mao, Yiwei; Hou, Shaodong; Chen, Yang; Liu, Xiaofen; Lou, Yang; Chen, Aichen; Yang, Luyun; Li, Jinyan; Dai, Nengli
Abstract : Highly enhanced photoluminescence of Eu 3+ achieved by co-doping SnO2 nanocrystals in mesoporous silica glasses. Abstract : This study reports the growth of SnO2 nanocrystals (NCs) in mesoporous silica glasses and its great enhancement of Eu 3+ photoluminescence at around 590 nm wavelength-band. Significantly different energy level character of Eu 3+ was observed using photoluminescence (PL) spectra, which was attributed to the effect of the SnO2 crystal field. Remarkably, enhancement of Eu 3+ as much as 116 times was achieved in the orange emission region by optimal SnO2 NCs addition. PL excitation spectra and decay curves verify the efficient energy transfer from SnO2 NCs to Eu 3+ . It is well understood that the highly enhanced emission originates from Eu 3+ embedded in SnO2 NCs and the strong energy transfer between them. Our study has not only demonstrated an effective way to enhance down-conversion PL of rare earth ions in silica glasses, but also widened the applications of semiconductor oxides such as SnO2 NCs.